Dioscin Protects ANIT-Induced Intrahepatic Cholestasis Through Regulating Transporters, Apoptosis and Oxidative Stress - Yao, Hong; Xu, Youwei; Yin, Lianhong; Tao, Xufeng; Xu, Lina; Qi, Yan; Han, Xu; Sun, Pengyuan; Liu, Kexin; Peng, Jinyong (Frontiers in Pharmacology, 2017)
Intrahepatic cholestasis is a clinical syndrome with systemic and intrahepatic accumulation of excessive bile acids that ultimately causes hepatobiliary injury. Appropriate regulation of bile acids in hepatocytes is critically important for protecting liver injury. We previously reported the effects of dioscin against α- naphthylisothiocyanate (ANIT)-induced cholestasis in rats. However, the pharmacolo- gical and mechanism data are limited. In the present work, liver injury in rats and mice were induced by ANIT, and dioscin was intragastrically administered for 7 days. In vitro, Sandwich-cultured hepatocytes (SCHs) were treated with dioscin before ANIT treatment. The results showed that dioscin markedly altered relative liver weights, restored ALT, AST, ALP, TBIL, GSH, GSH-Px, MDA, SOD levels, and rehabilitated ROS level and apoptosis. In mechanism study, dioscin not only significantly regulated the protein levels of Ntcp, OAT1, OCT1, Bsep and Mrp2 to accelerate bile acids excretion, but also regulated the protein levels of Bcl-2, Bcl-xl, Bax, Bak, Caspase 9 and Caspase 3 in vivo and in vitro to improve apoptosis. In addition, dioscin markedly inhibited PI3K/Akt pathway and up-regulated the levels of Nrf2, GCLc, GCLm, NQO1 and HO-1 against oxidative stress caused by bile acids. These results were further validated by inhibition of PI3K and Akt using the inhibitors of wortmannin and perifosine in SCHs. Our results suggested that dioscin exhibited protective effect against ANIT-induced intrahepatic cholestasis via regulating transporters, apoptosis and oxidative stress, which should be developed as one potent candidate for the treatment of intrahepatic cholestasis in the future.